Clinical research Determining entropy values equivalent to the bispectral index values during sevoflurane anaesthesia - BalcI, Canan; Karabekir, Hamit; Sivaci, Remziye (Archives of Medical Science, 2010)
Introduction: We aimed to identify the entropy levels that would be equivalent to the bispectral index (BIS) levels in sevoflurane anaesthesia in patients who are to undergo elective lumbar disc surgery. Material and methods: Thirty cases in ASA groups I-II who underwent lumbar disc surgery under general anaesthesia were included in our study after obtaining the consent of the patients and Ethics Committee of our medical school between January 1, 2005 and October 30, 2006. BIS and entropy electrodes were applied at the same time in 30 cases in the study group. The depth of the anaesthesia was regulated so that 10 min after beginning the general anaesthesia the BIS values were between 40 and 60. At the same time equivalent entropy values corresponding to BIS values were obtained. Results: At the end of the study, entropy values corresponding to general anaesthesia BIS values were identified. General anaesthesia BIS and RE/SE values at 10 min were lower than the values of the control, which was statistically significant (p < 0.05). Equivalent entropy values were obtained lower than the BIS values during general anaesthesia and these values were found to be statistically significant (p < 0.05). The blood pressure (BP) values obtained were very low at equivalent BIS values and when these BP values were compared with the initial BP values they were found to be statistically significant (p < 0.05). Conclusions: Based on this observation, we think that general anaesthetic agents that might cause severe hypotension could be more safely administered under entropy monitoring.